Zhang Fengchun jiang niao suan fang tong feng yin shi = Gout - Zhang, Fengchun, 1954- (Beijing: China Light Industry Press, 2022)
This book explains the misunderstanding of high uric acid and gout diet, and introduces how to eat, how to supplement, and what not to eat for patients with hyperuricemia and gout from many aspects such as nutrients, daily diet, Chinese herbal medicine, dietary details, diet and medication at different times, and what not to eat, how to eat scientifically, choose the right method, and prevent acute attacks and complications of gout.
Text in simplified Chinese scripts
Keywords: Gout -- Diseases -- Diet therapy -- Recipes; Gout -- Patients -- Nutrition; Cookbooks